Pengembangan Media Pembelajaran Monopoli Puisi pada Materi Menulis Puisi Siswa Kelas X Sekolah Menengah Atas Negeri 5 Kota Batam Tahun Ajaran 2022/2023 - Nurhalizah Safitri; Isnaini Leo Shanty; Tety Kurmalasari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research is a research and development (R&D) using the 4D model which consists of a defining stage consisting of defining, designing, and developing stages. This research aims to develop Monopoly Poetry learning media on writing material for grade X students of State Senior High School 5 Batam City in the 2022/2023 academic year. In this study, validity and practicality tests were carried out on the learning media developed. The definition of learning media using expert theory is, According to (Arsyad, 2015: 6) Learning media is a tool in the learning process that is used as communication and interaction between teachers and students in the learning process. While the definition of poetry using expert theory, namely, According to (Hidayatullah, 2017: 11) poetry is a literary work in the form of an outpouring of thoughts and feelings of a poet on the reality of life. Monopoly Poetry learning media is a visual learning media containing poetry material consisting of understanding, structure, types, language styles and questions. Monopoly Poetry learning media was validated by material experts and media experts, as well as practicality testing by teachers, small group students totaling 8 students and large group students totaling 40 students. Data collection techniques in this study were conducted by interview, media validity questionnaire and media practicality questionnaire. The data analysis technique in this study is descriptive qualitative to suggestions and input related to learning media and descriptive quantitative to analyze the assessment score of media validity and practicality. The results of this study are learning media Monopoly Poetry obtained a percentage of 87% with a qualification of "very valid" from media validation by media experts and obtained a percentage of 94% with a qualification of "very valid" from material validation by material experts. Furthermore, the practicality test was carried out with Indonesian language teachers of class X State Senior High School 5 Batam City obtained a percentage of 96% with the qualification "very practical". The practicality test of small group students obtained a percentage of 88% with the qualification "very practical" and the practicality test of large group students obtained a percentage of 89% with the qualification "very practical".